Assistance in Creating a Sustainibility Company Profile for MSME Jamu Marguno Bantul - Martinus Budiantara; Ratri Paramitalaksmi; Desak Putu Maharani (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
Kiringan, Bantul was named the Kiringan Jamu Tourism Village which was inaugurated in 2016. One of the MSMEs group in Kiringan is the MSME Jamu Marguno Group. The purpose of this assistance is to provide the necessary knowledge, skills, and support so that the family can manage the business finances and the family of Jamu Marguna entrepreneurs and provide the necessary understanding, skills, and support so that the accompanying business group can develop the business and assist the organization or community group of Jamu Marguna in improving their capacity, effectiveness, and performance